2002
DOI: 10.1097/00008469-200208000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cancer chemoprevention by hydroxytyrosol isolated from virgin olive oil through G1 cell cycle arrest and apoptosis

Abstract: Recent epidemiological evidence and animal studies suggest a relationship between the intake of olive oil and a reduced risk of several malignancies. The present study assesses the effect of hydroxytyrosol, a major antioxidant compound of virgin olive oil, on proliferation, apoptosis and cell cycle of tumour cells. Hydroxytyrosol inhibited proliferation of both human promyelocytic leukaemia cells HL60 and colon adenocarcinoma cells HT29 and HT29 clone 19A. The con-centrations of hydroxytyrosol which inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
143
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(157 citation statements)
references
References 35 publications
11
143
2
1
Order By: Relevance
“…The aglyconic form of oleuropein and ligstroside, 3,4-DHPEA-EA and p-HPEA-EA respectively, were reported for the first time by Montedoro et al, who also assigned their chemical structures, later confirmed by other (Montedoro et al, 1992;Angerosa et al, 1996;Owen et al, 2000). 3,4-DHPEA-EA and p-HPEA-EA, associated to the intense sensory of bitterness and pungency respectively attribute in VOO (Gutierrez-Rosales et al, 2003), is endowed with numerous beneficial effects on human health (Servili et al, 2004;Bendini et al, 2007;Esti et al, 1998;Della Ragione et al, 2000;Paiva-Martins et al, 2001;Fabiani et al, 2002;Carasco-Pancorbo et al, 2005;Artajo et al, 2006;Fabiani et al, 2006;Fabiani et al, 2008;Paiva-Martins et al, 2009). In particular, the anti-inflammatory properties of olive oil phenolic compounds seem to overlap with those attributed to non-steroidal anti-inflammatory drugs (Procopio A, et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…The aglyconic form of oleuropein and ligstroside, 3,4-DHPEA-EA and p-HPEA-EA respectively, were reported for the first time by Montedoro et al, who also assigned their chemical structures, later confirmed by other (Montedoro et al, 1992;Angerosa et al, 1996;Owen et al, 2000). 3,4-DHPEA-EA and p-HPEA-EA, associated to the intense sensory of bitterness and pungency respectively attribute in VOO (Gutierrez-Rosales et al, 2003), is endowed with numerous beneficial effects on human health (Servili et al, 2004;Bendini et al, 2007;Esti et al, 1998;Della Ragione et al, 2000;Paiva-Martins et al, 2001;Fabiani et al, 2002;Carasco-Pancorbo et al, 2005;Artajo et al, 2006;Fabiani et al, 2006;Fabiani et al, 2008;Paiva-Martins et al, 2009). In particular, the anti-inflammatory properties of olive oil phenolic compounds seem to overlap with those attributed to non-steroidal anti-inflammatory drugs (Procopio A, et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…In vitro and in vivo evidence has pointed out that phytochemicals affect a broad range of intracellular molecular targets. [3][4][5][6][7] In particular, polyphenols may exert anticancer effects by several mechanisms such as reducing the pro-oxidative effect of carcinogenic agents, 8,9 modulation of cancer cell signaling, 10,11 cell cycle progression, 12,13 promotion of apoptosis, 14,15 and modulation of enzymatic activities. 16 Regarding prostate cancer progression, a recent clinical trial assessed the effect of a polyphenol-blend dietary supplement over prostate-specific antigen (PSA) levels in men with localized prostate carcinoma; this study found a significant favorable effect on the percentage rise in PSA levels, an important indicator of prostate cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxytyrosol (3, and tyrosol (p-HPEA) are the most representative olive oil phenols present both as free compounds and linked to the dialdehydic form of elenoic acid (3,4-DHPEA-EDA and p-HPEA-EDA) . Previous studies carried out in our laboratory have showed that these compounds exert a pro-apoptotic activity toward cancer cell lines (Fabiani et al 2002(Fabiani et al , 2006. In particular, we have found that 3,4-DHPEA at high concentrations (100µM) induces apoptosis on HL60 cells through an oxidative stress caused by the extracellular production of hydrogen peroxide (H 2 O 2 ) (Fabiani et al 2008).…”
Section: Introductionmentioning
confidence: 84%